Orally administered low-molecular weight agaro-oligosaccharides are absorbed into the plasma of healthy humans - Shirai, Ikuya; Iwasaki, Yu; Karasawa, Koji; Shigemura, Yasutaka; Katayama, Shigeru (Frontiers in Nutrition, 2023)
Agaro-oligosaccharides (AOSs) are known to have biological activities, such as anti-inflammatory, anti-tumor, and anti-obesity effects. Although existing evidence suggests the presence of AOSs in peripheral tissues after oral administration, whether AOSs permeate into the blood circulation remains unknown. Thus, we hypothesized that AOSs with low-molecular weight can permeate the human gastrointestinal tract. To test this hypothesis, the time course of absorption was examined by analyzing plasma samples before and 1, 2, and 4 h after ingestion. Analysis was performed using liquid chromatography-mass spectrometry after labeling with p-aminobenzoic ethyl ester. Our results showed that the plasma concentration of agarobiose (Abi) was higher than that of agarotetraose (Ate); however, agarohexaose was not detected. Additionally, plasma levels of Abi and Ate were proportional to the dose. These results suggest that permeation efficiency is dependent on the molecular weight and that the systemic absorption of Abi via the gastrointestinal tract is better than that of Ate. These findings will contribute to a better understanding of the bioactivity of orally administered AOSs in peripheral tissues.Acetonitrile, ethanol, and formic acid were purchased from FUJIFILM Wako Pure Chemical Corporation (Osaka, Japan). Agar was provided by Ina Food Industry Co., Ltd. (Nagano, Japan). The AOSs were obtained by the hydrolysis of agar under mild acidic conditions, according to the method